Queue Based Energy Efficient Routing with Dynamic Resource Allocation in Mobile Adhoc Networks - Thebiga, M; Suji Pramila, R (International Journal of Engineering and Technology, 2018)
Mobile Adhoc networks (MANETs) is defined as an assembly of mobile nodes that are connected wirelessly in which they are dynamic in nature and form a short-term and non-permanent without the dependence of any framework or central supervision and management. Restricted battery potential is considered as one of the significant snag in mobile adhoc networks, as all the nodes included in the network will operate with restricted battery potential. Because of this restricted battery potential, it is mandatory to observe energy consciousness quality in our design. In this paper, we have addressed the energy efficiency in routing by examining the buffer queue status in sequence to avoid packet loss in networks. Finally, a dynamic resource allocation scheme is depicted to minimize the time complexity. In mobile adhoc networks, stabilizing energy and minimum energy utilization are considered as the prime necessity to elongate the existence of network. For this purpose Buffer queue based energy efficient routing algorithm is proposed. This algorithm will upgrade the quality and standard of network by minimizing energy consumption. Simulation results show that the proposed scheme has an efficient performance compared to conventional schemes.Â Â